Analisis Kesehatan Terumbu Karang Mengunakan Metode CPCE (Coral Point Count With Excel Extensions) di Perairan Pulau Popaya (Cagar Alam Mas Popaya Raja) Kabupaten Gorontalo Utara - Ridwan, Silvana Ariska; Baderan, Dewi Wahyuni K.; Katili, Abubakar Sidik (CV. ULIL ALBAB CORP, 2025)
Coral reefs are the main ecosystem of coastal waters and tropical seas, and their preseance is very dominant in coastal waters and small islands of the Indonesia archipelago. Coral reefs have a very large role, therefore damage to the coral reef ecosystem can result in disruption of all marine and coastal life in the region.CPCe (Coral Point Count With Excel Extensions) is used to observe coral reefs. The data used are the results of photos taken using the UPT (Under Photo Transect) method from 2 observation stations in the waters of Popaya Island (Mas Popaya Raja Nature Reserve). The photos consisted of 51 photos for each station. Photos taken with the assumption that they can represent each station used. Each photo processed in CPCe used 30 random points. The results showed that the highest percentage of coral cover was found at station 1 at 59,8% while the lowest percentage of coral cover was found at station 2 with a value of 35,75%. This shows that the level of damage that occurs in the waters of Popaya Island is higher at station 2.